HUBUNGAN JUMLAH SEL LIMFOSIT T CD8+ PADA ULKUS KAKI DIABETIK DERAJAT 3, 4, 5 DAN ULKUS NON DIABETIK - Putu Sutirta Yasa, I Wayan; Sudewa Djelantik, Anak Agung Gde; Suastika, Ketut; Mantik Astawa, Nyoma; Yuatmadja, Ignatius Ferdi (journal of internal medicine, 2009)
Diabetes mellitus (DM) is a complex metabolism disorder characterized by a severe chronic hyperglycemia with a largenumber of complications, diabetic foot ulcer (DF) is one of its disastrous progressive complication. It can cause a significantmorbidity if not treated adequately. Diabetic foot ulcer is very difficult to heal as it is generally associated with other co-morbidities,such as vassal complications (peripheral vassal disease) that may cause ischemia sufficient to damage many tissues in thebody. The excess of free radical products induces widespread inflammatory reactions. These conditions may also be exacerbatedby neuropathy and foot injury which directly cause the formation of DF. If the process is followed by infection, the inflammatoryreaction will be more severe. All these events will disrupt the normal immune response to participate in wound healing process.This cross sectional study was performed to determine CD8+ T lymphocyte count in diabetic foot ulcer graded 3, 4, and 5based on Wagner Ulcer Classification System (1989) and to test the hypothesis that CD8+ T cells count in DF grade 3, 4, and 5 islower than non-DM ulcer. As many as 11 patients with DF grade 3, 10 patients with grade 4, 7 patients with grade 5 were includedin this study. Sixteen patients with non-DM ulcer as control group. Red pea-shaped fresh ulcer tissues of lower extremity werecollected from each group for CD8+ T cell lymphocyte count and 2 cc blood were collected from vein for blood glucose examination.The result showed that CD8+ T cell count consistently decreased along with the increase of DF grade. The greatest countwas observed in non-DM ulcer {26/10 field view (10 fv)}, followed respectively by grade 3 (12/10 fv), 4 (8/10 fv), and 5 (6/10fv). Statistical analysis showed the difference in CD8+ T cell count among diabetic foot ulcer groups and foot ulcer non diabeticwas highly significant (p<0.05). The relationship between CD8+ T cell lymphocyte count among groups (Non-DM ulcer, DFgrade 3, 4, 5) based on Spearman Correlation test was 0.84 for CD8+ T cell lymphocyte (r = -0,846, p<0.001).